Dentin Thickness of Pulp Chamber Floor in Primary Molars: Evaluation by Cone-Beam Computed Tomography - Mariane Bovino; Larissa de Souza Santos; Larissa Lopes Freitas de Albuquerque Cavalcante; Cacilda Castelo Branco Lima; Marina de Deus Moura de Lima; Marcoeli Silva de Moura; Paulo de Tarso Silva de Macêdo; Lucia de Fátima Almeida de Deus Moura (Association of Support to Oral Health Research (APESB), 2021)
Objective: Use cone-beam computed tomography (CBCT) images to evaluate the dentin thickness of the pulp chamber floor in primary molars. Material and Methods: Cross-sectional study, conducted with CBCT images of teeth of children.  Primary molars with preserved pulp chamber floor were included. The dentin thickness of the pulp chamber floor in the primary molars was measured linearly in CBCT cross-sections. Data were descriptively analyzed and the Mann-Whitney test was applied (p<0.05). Results: 27 CBCT exams and 123 primary molars of children aged 4 to 13 years were analyzed; the majority was female (52.0%). In maxillary molars, the median dentin thickness was 1.50 (0.6-2.2) mm in the first and 1.65 (0.6-2.3) mm in the second (p=0.049) molars. In mandibular molars, the median was 1.20 (0.3-1.7) mm in the first and 1.60 (1.0-2.2) mm in the second (p<0.001) molars. Children aged 4 to 8 years showed less dentin thickness (p<0.001). Conclusion: The median dentin thickness of the pulp chamber floor in primary molars was 1.50 mm, ranging from 0.3 to 2.3 mm. Less dentin thickness was associated with younger children, teeth in the mandibular arch, and first molars.